Lessons From Heat Stroke for Understanding Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Stanculescu, Dominic; Sepúlveda, Nuno; Lim, Chin Leong; Bergquist, Jonas (Frontiers in Neurology, 2021)
We here provide an overview of the pathophysiological mechanisms during heat stroke and describe similar mechanisms found in myalgic encephalomyelitis / chronic fatigue syndrome (ME/CFS). Both conditions are characterized by disturbed homeostasis in which inflammatory pathways play a central role. Splanchnic vasoconstriction, increased gut permeability, gut-related endotoxemia, systemic inflammatory response, central nervous system dysfunction, blood coagulation disorder, endothelial-cell injury, and mitochondrial dysfunction underlie heat stroke. These mechanisms have also been documented in ME/CFS. Moreover, initial transcriptomic studies suggest that similar gene expressions are altered in both heat stroke and ME/CFS. Finally, some predisposing factors for heat stroke, such as pre-existing inflammation or infection, overlap with those for ME/CFS. Notwithstanding important differences – and despite heat stroke being an acute condition – the overlaps between heat stroke and ME/CFS suggest common pathways in the physiological responses to very different forms of stressors, which are manifested in different clinical outcomes. The human studies and animal models of heat stroke provide an explanation for the self-perpetuation of homeostatic imbalance centered around intestinal wall injury, which could also inform the understanding of ME/CFS. Moreover, the studies of novel therapeutics for heat stroke might provide new avenues for treatment of ME/CFS. Future research should be conducted to investigate the similarities between heat stroke and ME/CFS to help identify potential treatments for ME/CFS.